THE BULLYING IN THE VIEW OF HIGH SCHOOL'S STUDENTS (Fiep Bulletin - online, 2012)
Violence is something impregnated on our society, and the school inserted on this context is concerned on eliminate this problem of their environment. On this case, Bullying is a form of violence that permeates the school environment. The present study aims to evaluate the incidence of bullying among high school students of Belo Horizonte, Minas Gerais, as a start to the proposition of preventive and remedial education in the context of phenomenon. The research was developed from the application of semi-structured interview to 193 students visiting the event “Mostra das Profissões” at UFMG in 2010. After collection, we performed a quantitative and qualitative analysis of information obtained in the speech of the volunteers, on the theme of BULLYING at school. We use the technique of content analysis and divided the results into categories defined a priori.: Cat. 1: Knowledge about Bullying, Cat. 2: Knowledge about Bullying by gender, Cat. 3.: Impact on Physical Education classes, Cat. 4: Type of Bullying. As a result obtained by category: Cat 1: 63% knew what it was bullying, 28% did not know and 9% knew "more or less”. Cat.2: Females: 79 knew, 16 did not know and 7 knew "more or less." Males: 49 knew, 3 did not know and 8 knew "more or less”. Cat. 3: 59 young people revealed that there are Bullying in physical education classes, 127 revealed that there's not and 7 said they had no PE class. Cat.4: only 4% reported physical bullying, 69% reported verbal bullying, 11% said both and 16% did not identify the type. We conclude that there is a significant incidence of bullying among young people in school, that the act is present in physical education classes and that young people are aware of events.
Keywords: Bullying; young